Multiple Choice Objective Test Arabic Subject: Analysis & Implementation of the Edmodo Application/ Tes Objektif Pilihan Ganda Mata Pelajaran Bahasa Arab : Analisis & Implementasi pada Aplikasi Edmodo - Nodia Gustri Somahhida; Imam Makruf; Nadhimurridlo Al-Alwany (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This research aims to analyze the suitability of the questions with KI-KD and its implementation in the Edmodo application. The research method used is the descriptive qualitative method. Data was collected through documentation, interviews, and observation. The results of this study indicate that the objective test questions are under KI-KD. Inputting questions into the Edmodo application requires a lot of time, however, this application makes it easy for students to answer questions at a time that has been prearranged by the teacher.